Flouted Maxims in The Ellen Show: Kris and Kylie Jenner Interview (2023) - Rivaldo; Rekha Ramadhani Hidayat; Sarah Syenta Mutiara Jingga; Dwi Rahayu (Proceedings Series on Social Sciences & Humanities, 2024)
This research aims to identify a linguistic feature based on The Ellen Show with Kris and Kylie Jenner. The study employs a descriptive qualitative method, focusing on a transcript of his utterances and conversations. Grice's (1975) theory is applied to identify instances where conversational maxims are flouted during the interview. Grice's theory outlines four maxims that contribute to effective communication: quantity (supplying accurate information in the proper amount), quality (supplying accurate information), relevance (maintaining the subject), and manners (being brief and organized). The findings reveal six of the maxims of quantity, three of the maxims of quality, three of relevance, and eight of manner. The analysis shows that the most prevalent type is the flouting of the maxim of manner. It indicates that the maxim of manners is the one that gets violated the most frequently, which suggests that the conversation often lacks clarity and is characterized by overlapping speech and indirectness. This prevalence highlights that the interaction between Kris and Kylie Jenner on The Ellen Show tends to be less straightforward and more complex, with participants frequently speaking in ways that could be clearer and more orderly.